Teaching and Evaluating Oral Presentations on Family-Centered Rounds Using the FREE TIPSS Tool - Jared Austin; Tracy Bumsted; Chad Brands (Association of American Medical Colleges, 2013)
Abstract Introduction Presentations on family-centered rounds (FCR) provide a critical forum for information exchange, decision-making and teaching at the bedside. However, great variation exists in how this is done. This variation can lead to inefficient oral presentations on rounds, and frustration amongst learners, attending physicians and families. This tool is intended to aid clinician educators in teaching and evaluating medical students, interns, and residents on giving succinct, standardized bedside presentations on FCR. Methods This tool includes a facilitator's guide, a two-sided card featuring the FREE TIPSS mnemonic (Family/team introductions, Recap, Events overnight, Exam pertinents, Tests, Impressions, Problem-based plan, Staff input, Summary for family), scorecard assessment forms, and patient presentation examples. This tool is given to all pediatric interns and third-year medical students for use during their general inpatient pediatric rotations. This tool is also used individually with medical students and interns who struggle with oral presentations. Results We have successfully used this tool in our institution for the past 2 years. Prior to the initiation of this tool, we conducted a survey of our residents concerning guidelines and expectations for oral presentations of rounds on the general inpatient pediatric service. Three months after initiating this tool, we repeated the survey. The percentage of residents who reported clear guidelines and expectations of oral presentations increased from 79% before implementation to 91% after implementation. Discussion Since implementation, the FREE TIPSS tool has been used on our general inpatient pediatric service with positive feedback from residents, medical students, and faculty. While this module focuses on providing a standardized tool for oral presentations on rounds, it is important to allow some flexibility so that it may be adapted to the different needs of different rounding teams.